Effect of solvents on forming poly(butyl-2-cyanoacrylate) encapsulated paeonol nanocapsules. Issue 3 (11th February 2017) - Yao, Jingjing; Zeng, Decheng; Zhang, Yangxin; Sun, Dongdong; Yang, Endong; Liu, Haiping; Guo, Feng; Wang, Weiyun
Abstract: The effect of ethanol or acetone, as oil phase solvents, upon the form of paeonol-loaded poly(butyl-2-cyanoacrylate) encapsulated nanocapsules (Pae@PNCs) by interfacial spontaneously polymerization were investigated. Pae@PNCs characterizations including morphology, radius distribution, polydispersity index (PDI), particle size, zeta potential, entrapment efficiency (EE%), drug loading (DL%) and in vitro paeonol release kinetics were evaluated. Results show that 100% acetone have a significant effect on forming nanocapsules, which showed the smaller size (168.3 ± 6.76 nm) under scanning electron microscopy (SEM) and one radius distribution by the particle size analyser. The data showed that using 100% acetone to prepare Pae@PNCs was leading to smaller particle size and lower polydispersity index (PDI), higher zeta potential, better EE (%) and perfect DL (%), which is linear decrease in radius ( r 2  = 0.939) and PDI ( r 2  = 0.974) and linear increase EE% ( r 2  = 0.9879) and DL% ( r 2  = 0.9892) with the acetone concentration (range 10–100% v/v). Paeonol encapsulated into and adhered on PNCs were confirmed by UV–Visible spectra (UV–Vis), Fourier transform infrared spectroscopy (FTIR) and Differential scanning calorimetry (DSC). Drug release behavior in vitro showed that 100% acetone as solvents on developing Pae@PNCs have greater advantages in controlling and prolonging paeonol release. Results demonstrated that solvents have a significant influence on forming Pae@PNCs.